EDUKASI DAN STRATEGI PENGENDALIAN HAMA DAN PENYAKIT TANAMAN PALA DAN CENGKIH DI DESA LILIBOI - Patty, John Alfred (HIRONO : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve the community's knowledge and practical skills in identifying the main pests and diseases that attack nutmeg (Myristica fragrans) and clove (Syzygium aromaticum) plants. The activity was held in Liliboi Village, West Leihitu District, Central Maluku Regency, primarily targeting farmers experiencing serious problems related to declining production. Community participation in this activity demonstrated a high level of responsiveness, in line with the urgency of the problems faced, namely low crop quantity and quality. In some cases, clove harvests only occur every three years due to attacks by plant pests. This situation demonstrates the need to improve farmers' understanding of the main pests of nutmeg and clove plants and effective and sustainable control strategies.